Interventions in Pulmonary Medicine (Springer International Publishing, 2018)
This new edition offers comprehensive coverage of all areas of interventional pulmonology, a minimally invasive endoscopic method for diagnosing and treating lung disorders. The text is divided into eight sections on the major areas of interventional pulmonology, including basic endoscopy, lung cancer staging, and interventional bronschoscopy in asthma and emphysema. Chapters then explore specific procedures and techniques, including medical thoracoscopy, flexible and rigid bronchoscopy, endobronchial ultrasound, and electromagnetical navigation with coverage of history, indications and contraindications, and up-to-date evidence-based reviews. In recent years there have been many advances in interventional pulmonology, the most significant relating to lung cancer early diagnosis and late-stage treatment. Two new chapters on lung cancer epidemiologic changes and personalized lung cancer treatment explore new methods for maximizing patient care for an increasingly prevalent disease. This inclusive volume concludes with a look towards the future of interventional pulmonology and experimental techniques currently being tested. Interventions in Pulmonary Medicine, Second Edition, is a must have for pulmonologists, endoscopists, pulmonary oncologists, ENT physicians, thoracic surgeons, anesthesiologists, and intensive care specialists and their teams.